Tatwir Barnamij Wondershare Quiz Creator ‘ala al-Kitab al-‘Arabiyyah baina Yadaik Kamasdar Ta’lim al-Mustaqil - Yuniar, Yuniar; Hidayati, Fitri; Anggita, Tiya (Universitas Islam Negeri Raden Intan Lampung, 2020)
Wondershare Quiz Creator is a powerful test maker that allows trainers and educators to create professional flash-based multimedia tests and surveys. The research objectives are to know the sincerity and level of ease of use (Practically) and the effectiveness of the results of the development of the Wondershare Quiz Creator program on the Arabic book of Baina Yadaik as a source of independent learning in the cradle of Saad bin Abi Waqas Palembang. This research uses the research and development approach and then the data were analyzed three 1) design analysis 2) expert review 3) design revision, development. The research result are certification of materials is done with a very valid category of 74.47% and good 25.53%.It can be concluded that a program for a program Wondershare Quotes as an effective for use.Nobelty from this program is can be to make questions, tests, exams, and essay easily. Wondershare Quiz Creator has advantages compared to other programs that are the process of creating a similar problem in Microsoft Word.